An analysis of insider trading law and cases in the Malaysian securities markets - Yeon, Asmah Laili (2013)
The securities markets play a very significant role in the development of economic and business activities in the global environment. In Malaysia, it is evidenced through the achievement of the Malaysian capital market with fund raising approved by the Securities Commission Malaysia (SC) reaching RM118.93 billion at the end of 2011, compared to RM77.02 billion in 2010. In order to maintain investors confidence in the securities markets, there is a need for securities markets activities to be regulated and its must be rigorously enforced. Insider trading in securities markets is classified as one of the prohibited conduct under the Capital Markets and Services Act 2007 (CMSA 2007) of Malaysia. It is regulated under Sub Division 2, section 183 until 201 of the CMSA 2007. This paper critically analyzed the provisions of law and regulations and highlighted insider trading cases in Malaysia from the year 2010-2012. The source of legal data is from primary and secondary sources. The findings of research shows that the insider trading laws and enforcement are sufficient but there are a few improvements to be executed by the Securities Commission, self-regulatory bodies and corporations.